A revision of the taxonomic status of Xestotrogus Reitter, 1902 and related taxa, with the description of a new species from Iraqi Kurdistan (Coleoptera: Scarabaeidae: Melolonthinae) - Uliana, Marco; Khudhur, Farhad A. (Zootaxa, 2025)
An undescribed species of Rhizotrogini recently collected in Iraqi Kurdistan evidenced the unclear diagnosis of the genus-level taxa to which it could be attributed, prompting their revision. As a result, the currently monotypic subgenus Xestotrogus Reitter, 1902 is removed from subgeneric rank under the genus Xanthotrogus Reitter, 1902, treated as a valid genus and re-diagnosed. Cyprotrogus Nikolajev, 2004, also monotypic, is recognized as its junior subjective synonym. The new species, the third known of the genus, is then described as Xestotrogus sagrmaticus Uliana & Khudhur, new species. External morphology, aedeagus and endophallus of each species are illustrated.